A SILAR fabrication of nanostructured ZnO thin films and their characterizations for gas sensing applications: An effect of Ag concentration. (July 2020) - Devi, K. Radhi; Selvan, G.; Karunakaran, M.; Kasirajan, K.; Shkir, Mohd; AlFaify, S.
Abstract: Gas sensing device development is a key field of research in the recent scenario, Hence, in this work, facile fabrication of ZnO films with diverse content of Ag was accomplished as a vapor sensor using a cost-effective successive ionic layer adsorption and reaction (SILAR) process. X-ray diffraction (XRD) analysis provides evidence about the good crystalline nature of grown ZnO: Ag films and crystallite size was decreased from 38 to 27 nm with Ag content increased from 0 to 5 wt.%. Scanning electron microscope (SEM) analysis revealed the remarkable modification in morphology from nanograins (undoped) to nanorods (5 wt.% Ag). Energy dispersive analysis of X-rays (EDX) supports the Zn, O, and Ag content present in the final film. The prepared Ag-doped ZnO films exhibited good optical nature and an improvement in the energy gap from 3.04 to 3.29 eV was noticed. The responsivity, response and recovery time of ammonia vapor sensor were remarkably enhanced to 8260 %, 27 s, and 7 s respectively, for the 5 wt.% Ag doped ZnO nanofilm. The responsivity of 5 wt.% Ag doped film was 15 times that of undoped ZnO film. These results make low cost grown Ag-doped ZnO nanorod a good candidate for high quality vapor sensor. Highlights: Facile fabrication of ZnO:Ag films-based ammonia gas sensor has been achieved by SILAR route. XRD and FT-Raman confirm the monophasic hexagonal ZnO formation. Morphology was remarkably transformed from nanograins to nanowires. An improvement in energy gap from 3.04 to 3.29 eV in ZnO was noticed when doped with Ag. Fabricated ZnO film with 5 wt% Ag is highly sensitive to sensing ammonia gas.